Development and evaluation of power consumption model for no-till planter based on working parameters - Dongming, Gao; Lianhao, Li; Xiaodong, Qiao; Sarker, Khokan Kumer (International Journal of Agricultural and Biological Engineering, 2017)
In order to fully understand the relationships of power consumption of no-till planter among tractor, soil properties and working parameters which affect the field operation, the power consumption model for no-till planter applied to overcome the coupling difficulties was developed in the study. Based on operation depth of no-till planter and soil properties as constraints in accordance with a certain distribution, we collected and analyzed the relationship data among traction force, forward speed and power output shaft by field test. The results showed that the relationship between traction power and power-take-off (PTO) power was negatively correlated. Under the same power consumption condition, the relationship between traction force and the PTO torque was linearly correlated, and the slope was basically consistent. Different power consumptions corresponded to different intercepts. When the forward speed was 6-7 km/h and PTO shaft rotational speed was 370-450 r/min, lower power consumption with higher working efficiency can be achieved. There was a direct correlation between total power consumption and the square of rotational speed multiplied by forward speed. The maximum correlation coefficient was found around 0.82. The findings set up a foundation for designing control system of no-till planter.Keywords: no-till planter, power consumption, models, working parameters, evaluationDOI: 10.3965/j.ijabe.20171001.2310Citation: Gao D M, Li L H, Qiao X D, Sarker K K. Development and evaluation of power consumption model for no-till planter based on working parameters. Int J Agric & Biol Eng, 2017; 10(1): 80–87.